21st Century Learning and Smartphone Preference as a Learning Media - Ifham Choli; Ahmad Mujib; Eddy Saputra; Fery Rahmawan; Marliza Oktapiani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
Smartphones are a technological device that is very close to students nowadays, but there are still many negative views regarding their use. 21st century education demands a transformation in learning methods to accommodate developments in information technology in the learning process. One tool that is increasingly dominant in everyday life is the smartphone. This article discusses the integration of 21st century learning with the preference for using smartphones as a learning medium in the school environment. This research explores the impact of smartphone use on student learning, involving factors such as technology availability and student responses to smartphone-based learning. The research was conducted at Indraprasta University, PGRI Jakarta. The research method used was a descriptive-qualitative approach. Qualitative research aims to understand, explain, and describe phenomena or problems from a more in-depth perspective. This research aims to prepare students to maximize the use of smartphones as a support for 21st century learning. This research shows that using smartphones as a learning medium can improve the quality of learning and develop 21st-century skills such as critical, creative, collaborative, and communicative.